The Eco-Efficiency Level Analysis at Various Scales of Robusta Coffee Production of Argopuro Mountain, Jember, Indonesia, Based on Life Cycle Assessment. - Purnomo, Bambang Herry; Novita, Elida; Bagus Suryaningrat, Ida; At-Ta’anny, Ummu (Indonesian Coffee and Cocoa Research Institute, 2025)
Ground coffee is one of the high value added downstream coffee products that can be developed to increase the income of coffee processors. However, there are concerns about the increasing environmental impact of the downstream process into ground coffee, so it is necessary to evaluate the impact from environmental and economic aspects. The Argopuro robusta coffee processing business in Jember Regency is trying to be developed towards downstream products to increase the income of coffee farmers. Of course the negative impact on the environment must be considered. The aim of this research are first, to determine the environmental impacts that occur in the robusta ground coffee production process; second, to determine the level of eco-efficiency of the robusta ground coffee production process; and third, knowing how to compare the environmental impact and level of eco-efficiency at various scales of ground coffee production. The method used is life cycle assessment (LCA) with a scope from caring for coffee plants to delivering coffee products to consumers. The impact measured is for every one hectare of harvest. The research sample is a Argopuro robusta coffee processing unit that produces green beans and ground coffee. The higher the scale of ground coffee production, the higher the CO2 eq emissions. However, the added value is also getting higher. Eco-efficiency calculations show that if the coffee harvest (6 tons/ha) is converted all into ground coffee, it produces emissions of 1086 Kg CO2eq and a profit of 144.1 million with an eco-efficiency index value of 97.42 and is included in the classified as affordable and sustainable. This value does not differ if the ground coffee conversion scale is 20% or 50%. This indicates that the conversion of ground coffee to maximum scale in robusta coffee processing businesses is still considered environmentally sustainable.